2015
DOI: 10.1039/c5dt03257a
|View full text |Cite
|
Sign up to set email alerts
|

Insertion and isomerisation of internal olefins at alkylaluminium hydride: catalysis with zirconocene dichloride

Abstract: The insertion of internal olefins (hydroalumination) and chain walking isomerisation at di-n-octylaluminium hydride [Al(Oct)2H], promoted by zirconocene dichloride [Cp2ZrCl2] has been studied. The reaction between [Cp2ZrCl2] and [Al(Oct)2H] in non-polar solvents leads to clusters containing bridging hydride ligands between Zr and Al. This system promotes hydroalumination of 1-octene but is largely ineffective for internal octenes (2-, 3-, 4-octene). In tetrahydrofuran the Zr-Al hydride clusters formed are more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…These preliminary mechanistic studies in THF also revealed that a mixed metal hydride should be involved. However, since Zr/Al clusters have not been identified in THF, , we wanted to transpose the de- O -acetylation reaction in toluene to identify the active species. Indeed, in this apolar solvent, extensive structural and reactivity studies have been performed to rationalize zirconium-catalyzed hydroalumination of alkenes by mixtures of Cp 2 ZrCl 2 and aluminum hydrides .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These preliminary mechanistic studies in THF also revealed that a mixed metal hydride should be involved. However, since Zr/Al clusters have not been identified in THF, , we wanted to transpose the de- O -acetylation reaction in toluene to identify the active species. Indeed, in this apolar solvent, extensive structural and reactivity studies have been performed to rationalize zirconium-catalyzed hydroalumination of alkenes by mixtures of Cp 2 ZrCl 2 and aluminum hydrides .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of clusters from mixtures of Cp 2 ZrCl 2 and organoaluminum compounds in THF has previously been monitored by 1 H NMR spectroscopy, but the structure of these aggregates remains elusive in this polar solvent . On the other hand, several zirconium/aluminum mixed metal hydrides were fully characterized in apolar solvents, and extensive reactivity studies revealed their critical role in zirconium-catalyzed hydro- and carboaluminations of alkenes and alkynes .…”
Section: Introductionmentioning
confidence: 94%
“…15,[38][39][40][41][42] This may be one reason for the poor performance of this system in hydroalumination, relative to hydroboration. While the Co-hydride signal appears as a single peak, the ligand resonances show that two very similar species are present, a major and a minor component.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] The cycle relies on the tendency of some transition metal and group 13 metal secondary alkyls to rearrange to the thermodynamically preferred primary alkyl by way of chain walking. [13][14][15] The cycle relies on the tendency of some transition metal and group 13 metal secondary alkyls to rearrange to the thermodynamically preferred primary alkyl by way of chain walking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation